The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1021/ed400477b
|View full text |Cite
|
Sign up to set email alerts
|

Paying Attention to Gesture when Students Talk Chemistry: Interactional Resources for Responsive Teaching

Abstract: When students share and explore chemistry ideas with others, they use gestures and their bodies to perform their understanding. As a publicly visible, spatio−dynamic medium of expression, gestures and the body provide productive resources for imagining the submicroscopic, three-dimensional, and dynamic phenomena of chemistry together. In this paper, we analyze the role of gestures and the body as interactional resources in interactive spaces for collaborative meaning-making in chemistry. With our moment-by-mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 77 publications
(94 reference statements)
0
50
0
2
Order By: Relevance
“…We have suggested two. First, if we consider mathematical actions as a kind of thought, we raise questions about the nature of knowledge in a social and material context, a topic we have discussed previously [39,53,54]. Second, an awareness of the variability in students' mathematical thinking is an essential element of advanced physics instruction.…”
Section: Discussionmentioning
confidence: 99%
“…We have suggested two. First, if we consider mathematical actions as a kind of thought, we raise questions about the nature of knowledge in a social and material context, a topic we have discussed previously [39,53,54]. Second, an awareness of the variability in students' mathematical thinking is an essential element of advanced physics instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Revoicing occurs in many educational contexts (from kindergarten [Yifat & Zadunaisky-Ehrlich, 2008] to undergraduates [Flood et al, 2015]) and across a wide variety of subjects (from mathematics [Krussel & Edwards, 2004] and science [e.g., Ruiz-Primo & Furtak, 2007] to second-language learning [e.g., Park, 2013] and liberal arts seminars [Parsons, 2017]). Scholars argue that revoicing is pedagogically advantageous because it can (a) promote deeper full-class exploration of student-generated ideas [Forman & Ansell, 2002], (b) highlight particular elements of student ideas while backgrounding other elements [Nam, Ju, Rasmussen, Marrongelle, & Park, 2008], (c) extend and reshape the content of student contributions to resemble disciplinarily normative concepts [Eckert & Nilsson, 2017], (d) help students adopt disciplinarily normative language and representations [Forman & Larreamendy-Joerns, 1998], and (e) promote participation by explicitly valuing and soliciting student contributions [Strom, Kemeny, Lehrer, & Forman, 2001].…”
Section: Ethnomethodological Conversation Analysis and Co-operative Amentioning
confidence: 99%
“…Guided by the recent emphasis on the examination of multimodal interactions (e.g., Birchfield et al [25], Flood et al [27], Pogue & Ahyun [33]), we initially observed the selected videos in order to characterize the types of multimodality that students experience in the embodied learning environment; that is, verbal and non-verbal interactions.…”
Section: Methodsmentioning
confidence: 99%
“…Multimodal instruction emphasizes the value of effectively integrating representations of content across multiple sensory modalities to facilitate understanding and discourse [25][26][27][28]. These modalities can take on many forms, and while classification varies, Prain and Waldrip [29] provided a broad framework: descriptive (verbal, graphic, tabular), experimental, mathematical, figurative (pictorial, analogous, or metaphoric), and kinesthetic (gestural).…”
Section: Embodiment and Multimodal Learningmentioning
confidence: 99%
See 1 more Smart Citation